Atomic and nano-scale characterization of a 50-year-old hydrated C3S paste. (November 2015) - Geng, Guoqing; Taylor, Rae; Bae, Sungchul; Hernández-Cruz, Daniel; Kilcoyne, David A.; Emwas, Abdul-Hamid; Monteiro, Paulo J.M.
Abstract: This paper investigates the atomic and nano-scale structures of a 50-year-old hydrated alite paste. Imaged by TEM, the outer product C–S–H fibers are composed of particles that are 1.5–2 nm thick and several tens of nanometers long. 29 Si NMR shows 47.9% Q1 and 52.1% Q2, with a mean SiO4 tetrahedron chain length (MCL) of 4.18, indicating a limited degree of polymerization after 50 years' hydration. A Scanning Transmission X-ray Microscopy (STXM) study was conducted on this late-age paste and a 1.5 year old hydrated C3 S solution. Near Edge X-ray Absorption Fine Structure (NEXAFS) at Ca L3, 2 -edge indicates that Ca 2 + in C–S–H is in an irregular symmetric coordination, which agrees more with the atomic structure of tobermorite than that of jennite. At Si K-edge, multi-scattering phenomenon is sensitive to the degree of polymerization, which has the potential to unveil the structure of the SiO4 4 − tetrahedron chain.